Penggunaan Instagram Terhadap Perilaku Flexing Mahasiswa Universitas Muhammadiyah Riau Pekanbaru - nazhifah, nazhifah (Jurnal Paradigma, 2024)
This article discusses the influence of Instagram use on flexing behavior in students. Flexing behavior as a form of showing off possessions on social media aims to gain appreciation, honor, and social status where the wealth owned is not necessarily true of the ownership of one's own assets. The method used is descriptive of quantity. This research uses secondary data techniques by analyzing photos or videos on social media based on criteria. The results showed that the correlation analysis between social media variables and flexing behavior was (r) = 0.347, then the level of influence strength between variables was in the interval 0.40 – 0.599, This means that there is an influence in the medium category between social media on flexing behavior in students of the University of Muhammadiyah Riau in Pekanbaru.